Indicatory external findings in two cases of fatal cervical spine injury - Schwarz, Clara-Sophie; Uebbing, Katrin; Germerott, Tanja; Krauskopf, Astrid (Journal of forensic and legal medicine, 2020)
A fatality of an 83-year-old female experiencing acute circulatory failure as a result of a type II odontoid fracture is compared with the case of an 86-year-old female who died from delayed cardiopulmonary complications due to a lower cervical spine injury. Falls on the forehead from minor height can cause odontoid fractures especially in elderly patients, hyperextension of the neck on the other hand can lead to lower cervical spine injury with prevertebral hematoma. The latter can lead to extensive hematoma of the neck, but might be difficult to diagnose by computed tomography in the living patient. Especially in cases of elderly patients showing bruises on the forehead or extensive neck hematoma, the possibility of cervical spine fracture should be taken into account and postmortem examinations should be arranged commensurately.